The pectoralis myofascial flap in laryngeal surgery - Özkul, Yılmaz; Songu, Murat; Arslanoğlu, Seçil; Dündar, Rıza; Uçar, Mehmet; Pınar, Ercan; Önal, Kazım (ENT Updates, 2014)
Objective: To report our experience about pedicled pectoralis major myocutaneous flap (PMMF) for the treatment of pharyngocutaneous fistula (PCF). Methods: Between June 2006 and September 2014, 202 consecutive total laryngectomies for laryngeal or hypopharyngeal squamous cell carcinoma were performed in our hospital. The medical records of the patients were retrospectively reviewed to document the development of a PCF. Results: PCF developed in 45 of 202 patients (22%) in the study group. Of these 45 patients, spontaneous closure with local wound care was achieved in 33 patients (73%). Remaining 12 patients required surgical closure with PMMF. Four of 12 patients (25%) had complications after surgical closure with PMMF. Radiotherapy had been performed before laryngectomy in 16 of 45 patients with PCF. Of these 16 patients who developed PCF and have had previous radiotherapy, spontaneous closure with local wound care was achieved in four cases, while PMMF was used in the remaining 12 cases. Conclusion: Pedicled pectoralis major myocutaneous flap is a good reconstructive option in the treatment of PCF formation following total laryngectomy surgery.